Levels and determinants of perceived health risk from solid wastes among communities living near to dumpsites in Kenya. Issue 4 (3rd July 2020) - Amugsi, Dickson A.; Haregu, Tilahun Nigatu; Mberu, Blessing U.
ABSTRACT: Many countries in sub-Saharan Africa have poor solid waste management systems, putting people living near dumpsites at higher risk of disease infections. Good risk perception could enhance individual- and community-level protection and prevention efforts. The objective of this study was to examine the levels and determinants of perceived health risk associated with exposure to solid waste dumpsites in Kenya. The level of risk was measured on a five-point Likert scale. The results showed that about 27% and 42% of the study population in Nairobi and Mombasa, respectively, perceive that they have little or no health risk from the nearby dumpsites. Study site, family size and wealth index were associated with risk perception in the multivariate analysis. A sizable proportion (42%) of the population living near dumpsites has lower risk perception. Health promotion interventions are needed to enhance risk awareness and perception in these communities.